2016
DOI: 10.1038/srep37845
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-mediated autophagy decreases sensitivity to oxymatrine in SW982 human synovial sarcoma cells

Abstract: Oxymatrine (OMT) is a type of alkaloid extracted from a traditional Chinese medicinal herb, Sophora flavescens. Although the antitumor activities of OMT have been observed in various cancers, there are no reports regarding the effects of OMT on human synovial sarcoma. In the present study, we analyzed the antitumor activities of OMT in SW982 human synovial sarcoma cells and determine whether high mobility group box protein 1 (HMGB1)-mediated autophagy was associated with its therapeutic effects. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Under normal conditions, autophagy protects cells against pro-apoptotic factors ( 45 , 46 ). However, autophagy can also play a role similar to apoptosis, leading to autophagic cell death in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, autophagy protects cells against pro-apoptotic factors ( 45 , 46 ). However, autophagy can also play a role similar to apoptosis, leading to autophagic cell death in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a survival strategy employed by cells experiencing nutrient deprivation or other stresses, which is a tightly regulated by the lysosomal degradation pathway, and is considered to be essential for cell growth, differentiation, development, survival and homeostasis. However, while autophagy is generally considered to be a survival mechanism under normal homeostatic conditions, it has both pro-death and pro-survival roles in cancer (21,23). Chemotherapeutic drugs can induce both apoptosis and autophagy in the treatment of cancer, and it was previously reported that autophagy helps cancer cells evade apoptosis, and thus contributes to chemoresistance (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated the cytoprotective role of autophagy in response to 5-FU treatment in gastric cancer cells (27,28), while a different study showed that 5-FU may suppress miR-30 to upregulate beclin-1 and thus induce autophagic cell death and cell proliferation arrest in gastric cancer cells (29). Nevertheless, many studies have shown that autophagy protects various tumor cells against apoptosis induced by chemotherapeutic drugs (23,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some studies indicated that oxymatrine may prevent pulmonary hypertension through its anti-proliferative, anti-inflammatory, and antioxidant effects 10 . Oxymatrine can induce apoptotic cell death of human pancreatic cancer 11 and prostate cancer 12 Some research found that oxymatrine combining HMGB1 may be more effective in the treatment of human synovial sarcoma and oxymatrine may induce autophagy 13 . These studies suggested that matrine and oxymatrine may be effective in anti-tumor activities.…”
Section: Introductionmentioning
confidence: 99%